Plant-wide MPC control scheme for CO2absorption/stripping system - Sultan, T. (Elsevier Ltd, 2019)
The high contents of CO2in natural gas processing industries cause various issues in the operation, and it is essential to reduce the amount of CO2using amine-based absorption processes. An efficient and flexible control strategy is highly desirable for CO2removal in CO2absorption/stripping system. The excellent performance of Model Predictive Control (MPC) in setpoint tracking and disturbance rejection scenarios could make it a better option for the flexible controllability of a CO2absorption/stripping plant. MPC performance depends significantly on the accuracy of the identified mathematical model of the plant. The state-space model is believed as the better option for MPC as it represents the plant model with true dynamics. Therefore, this study is focused on the design of the 2 Ã 2 MPC control strategy in MATLABÂ® MPC Designer Toolbox using 2nd order continuous-time state-space model. The main aim of this study is to develop a plant-wide control scheme based on MPC for the natural gas absorption/striping system. Step changes in the CO2composition of sweet gas (Â±5) and stripper temperature (Â±15) have been introduced in the absorption/stripping simulation model. The results show that the MPC controller has achieved the new setpoint of CO2composition within 0.5 sec in the setpoint tracking scenario. Similarly, the MPC controller has been able to reject the disturbances successfully introduced as Â± 15 step change in stripper temperature within 7.5 sec. Hence, the performance of the MPC controller using the state-space model at higher step changes is adequate with no peak, closer to the setpoint, and no overshoot in the output. Â© 2019 Elsevier Ltd. All rights reserved.